Sorption in 2020s - Kyzas, George; Lazaridis, Nikolaos (IntechOpen, 2020)
The book deliberately keeps background information to a minimum, instead it comprehensively covers adsorption of liquid solutions, the difference between equilibrium individual solute uptake and surface excess, a general discussion of adsorbate uptake mechanisms and uptake rate expression, uptake steps, performance models and their generalizations, application of performance models, and design methods based on the constant behavior assumption, and the unused bed length concept.